Some parseval-goldstein type identities with illustrative examples - KARATAŞ, HİLAL BAŞAK; ALBAYRAK, DURMUŞ; UÇAR, FARUK (My University, 2023)
In the present paper, the integral transform which will be called generalized Laplace transform is considered. Iteration of generalized Laplace transform and Fourier cosine transform and Fourier sine transform is generalized Glasser transform. Some identities involving these transforms and the Mellin transform and the generalized Stieltjes transform are given.
Keywords: Temel Bilimler (SCI); Matematik; Natural Sciences (SCI); MATHEMATICS; Genel Matematik; Fizik Bilimleri; General Mathematics; Physical Sciences; Fourier cosine transforms; Fourier sine transforms; Generalized Glasser transforms; Generalized Laplace transforms; Generalized Stieltjes transforms; Mellin transforms; Parseval-Goldstein type theorems